Impact of polygenic risk score (PRS) for coronary artery disease on physician decision-making and patient care - Ntritsos, Georgios; Ornan, Erez; Gamliel, Nir; Chernin, Gil; Pallay, Arnold; Chen, Michael; Kessous, Efi; Feldhay, Eran (Frontiers in Genetics, 2025)
IntroductionPolygenic risk scores (PRS) have emerged as a promising tool for refining cardiovascular risk prediction, yet their real-world impact on physician decision-making remains unclear. This study aimed to evaluate how the integration of a coronary artery disease (CAD) PRS with traditional clinical risk factors influences physician management strategies.MethodsWe conducted a multicenter, prospective, open-label pilot study across three clinical sites. A total of 150 patients (aged 18–55 years, LDL-C ≤130 mg/dL, no history of diabetes or coronary artery disease) were recruited. Buccal swabs were collected for PRS analysis, and results were integrated with clinical data to generate personalized risk profiles. Physicians utilized these profiles during consultations and completed structured feedback surveys assessing PRS influence on their clinical decisions.ResultsPRS findings impacted clinical decision-making in 67% of cases (100 participants). The most frequent physician response was raising patient awareness and offering patient education (73 cases), while emphasizing PRS as a tool for risk communication. In 4 specific cases, PRS findings led to new statin recommendations, while 23 cases resulted in other management modifications, including lifestyle adjustments and increased risk monitoring.DiscussionThese findings highlight the potential of PRS in enhancing risk communication and clinical decision-making, primarily by reinforcing patient awareness rather than directly by altering pharmacologic management. Further research is needed to optimize PRS implementation and assess its long-term clinical impact.